Reducing Impulsive Choice: VI. Delay-Exposure Training Reduces Aversion to Delay-Signaling Stimuli - Peck, Sara (Psychol Addict Behav, 2019)
Delay-exposure (DE) training consistently and robustly reduces impulsive choice in rats, but the behavioral mechanisms behind this effect are not yet understood. The present study evaluated if DE training works by mitigating aversion to delay-signaling stimuli – those encountered when rats chose the larger-later reward in impulsive choice assessments. Fifty-seven rats were randomly assigned to 120 days of training with delayed reinforcement (DE), training with immediate reinforcement (IE), or to a no training Control group. Consistent with prior experiments, DE rats made significantly fewer impulsive choices than IE or Control rats. Subsequently, in a separate assessment of delay aversion, rats were given the opportunity to press a lever to temporarily escape from stimuli correlated with long or short time-intervals to food. When these escape opportunities terminated delay-signaling stimuli in the impulsive-choice task, DE rats escaped significantly less than IE and Control rats. When escapes terminated FI-signaling stimuli (a procedure in which there is no response-reinforcer delay), the difference only approached significance. These results support the hypothesis that DE training reduces impulsive choice, in part, by reducing aversion to delay-signaling stimuli.